2020
DOI: 10.1002/prep.202000187
|View full text |Cite
|
Sign up to set email alerts
|

Heat of Formation of Triazole‐Based Salts: Prediction and Experimental Validation

Abstract: This work contributes to the growing interest in predictions linked with energetic salts. A reliable method to accurately compute the heat of formation of triazole-based salts was investigated. Calculations were based on Born-Haber energy cycles: gas-phase enthalpy of ions and lattice enthalpy were calculated separately. Ten triazole-based salts were synthesized and fully characterized. Their heat of combustion was measured by bomb calorimeter. Gas-phase heat of formation of cations and anions were computed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In the fundamental work of Curtiss [12], a thorough analysis of the accuracy of quantum-chemical calculations of thermochemical quantities on the example of 454 structures was performed using the G4 method within the Gaussian software, and it was shown that the average deviation of the calculation results from the experimental values in this case was only 0.8 kcal/mol, which for high-enthalpy substances was less than 1%. Over the past 15 years, many studies [13][14][15] of the approaches to calculate ∆H • f for a wide range of substances of various classes, using high-level calculations, have shown that methods of the Gaussian family, in particular G4, are effective to estimate ∆H • f of high-energy polynitrogen compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In the fundamental work of Curtiss [12], a thorough analysis of the accuracy of quantum-chemical calculations of thermochemical quantities on the example of 454 structures was performed using the G4 method within the Gaussian software, and it was shown that the average deviation of the calculation results from the experimental values in this case was only 0.8 kcal/mol, which for high-enthalpy substances was less than 1%. Over the past 15 years, many studies [13][14][15] of the approaches to calculate ∆H • f for a wide range of substances of various classes, using high-level calculations, have shown that methods of the Gaussian family, in particular G4, are effective to estimate ∆H • f of high-energy polynitrogen compounds.…”
Section: Introductionmentioning
confidence: 99%